A food monitoring system for preventing product deterioration. (1st January 2014) - Choy, K.L.; Lam, H.Y.; Lee, C.K.M.; Chin, K.S.; Ip, W.H.; Poon, T.C.
A food warehouse is an essential buffer which controls the key factors like temperature, pallet load pressure, humidity and maintains food quality and food safety. However, the traditional method of adopting a warehouse management system may not be sufficient for managing a food warehouse as it lacks temperature and pressure monitoring ability. In this paper, an effective monitoring system, adopting radio frequency identification (RFID), is proposed to provide timely and accurate information in controlling the warehouse environment and product quality in a food warehouse by formulating a reliable procedure to prevent food from deterioration. The system is also able to tackle the problem of the influence of liquid on RFID, and will provide quality control alerts in real-time supervision. Through applying the proposed system in a case company, it is proved that EMS significantly reduces the amount of deteriorated/inferior products as well as reducing the cost of quality control.